2020
DOI: 10.1093/bioinformatics/btaa274
|View full text |Cite
|
Sign up to set email alerts
|

OpenBioLink: a benchmarking framework for large-scale biomedical link prediction

Abstract: Abstract Summary Recently, novel machine-learning algorithms have shown potential for predicting undiscovered links in biomedical knowledge networks. However, dedicated benchmarks for measuring algorithmic progress have not yet emerged. With OpenBioLink, we introduce a large-scale, high-quality and highly challenging biomedical link prediction benchmark to transparently and reproducibly evalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 8 publications
(8 reference statements)
0
52
0
Order By: Relevance
“…We demonstrated that this approach outperforms competing methods, and more detailed analysis showed it is particularly beneficial when the data attributes are informative. Future work will evaluate the efficacy of our approach for more comprehensive knowledge graphs, such as the recent OpenBioLink (Breit et al , 2020) dataset. Further, it is well known (Kadlec et al , 2017) that hyperparameter tuning can lead to significant performance gains for many methods; thus, future work will also incorporate hyperparameter optimization strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that this approach outperforms competing methods, and more detailed analysis showed it is particularly beneficial when the data attributes are informative. Future work will evaluate the efficacy of our approach for more comprehensive knowledge graphs, such as the recent OpenBioLink (Breit et al , 2020) dataset. Further, it is well known (Kadlec et al , 2017) that hyperparameter tuning can lead to significant performance gains for many methods; thus, future work will also incorporate hyperparameter optimization strategies.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, it is expensive to identify novel relations and most of them are still unknown. Recently, a variety of similar biomedical KGs have been proposed, such as (Breit et al, 2020) and (Mohamed et al, 2020). Due to the similarity of the source databases, we do not further consider those here; nevertheless, DOUBLER can be directly applied to those KGs, as well.…”
Section: Biomedical Knowledge Graphmentioning
confidence: 99%
“…Third, in the field of research, professional findings and co-authors interactions in any research area [9]. Certainly, the link prediction method can be used in biology and biomathematics [6], for example, in gene expression network and health care a, specialists predicting about outmost probability which reversals near future possibilities and managing them in proportion by communication with related people through online and off-line social network.…”
Section: Figure 1 Example Of Link Predictionmentioning
confidence: 99%
“…The first network, OpenBioLink, is a large-scale KG generated from an integrative effort designed to establish a benchmark dataset for link prediction [39]. The second is an In-House network that is comprised of tens of thousands of interactions from eight databases that we have harmonized for this work including PathMe [40][41][42][43], BioGrid [44], IntAct [45], and PathwayCommons [46] for protein-protein relations, DrugBank [47] for drug-protein relations, and DisGeNet [26] for protein-indication interactions.…”
Section: Case Scenariosmentioning
confidence: 99%